Remoção de corantes têxteis via adsorção em nanotubos de carbono de paredes múltiplas comerciais e quimicamente modificados - Letieri Fernandes Pessoa (2016)
In this work, a new adsorption method for the removal of the textile dye compounds Reactive Red 195 (RR) and Direct Orange 39 (DO) using multi-walled carbon nanotubes (MWCNT) was developed. Three types of MWCNT were evaluated: two of them were purchased commercially (CTUBE e SKU) and one was obtained through the chemicalmodification (acid treatment) of the nanotube SKU, producing a new material, called SKU-f. The MWCNT were characterized by thermogravimetric analysis, Raman spectroscopy, Transmission electron microscopy and adsorption/desorption of N2. Firstly, the influence of the pH and kinetic of adsorption were investigated for the optmization ofthe method and the best efficiency of removal was found at pH 1.00 and 3.00. In the kinetic study, the thermodynamic equilibrium of adsorption was achieved after 10 minutes of manual agitation of the assays, with low variation of the quantities of dye compounds adsorbed on the MWCNT surface. Moreover, the experimental isotherms were obtained for RR and DO for all adsorbents and the adsorption process was betterfitted to the Langmuir Model. The maximum adsorption capacities were 199.20 mg g-1 and 173.91 mg g-1 for RR and DO, respectively, both in CTUBE. Finally, a real sample of textile effluent was analyzed and a discoloration rate of 97.81% were obtained, noting the efficiency of MWCNT and the use as an promising alternative for the treatment thiskind of industrial effluent.